PENGARUH LITERASI KEUANGAN TERHADAP KETAHANAN UMKM PANGAN DALAM PEMANFAATAN FINTECH PADA PELAKU USAHA KOTA BLITAR - Eko Wahyu Budiman; Tri Kurniastuti (Universitas Tribhuwana Tunggadewi, 2025)
This study aimed to examine the influence of financial literacy on the resilience of food-sector MSMEs (Micro, Small, and Medium Enterprises), with fintech adoption as a supporting variable, to address the research gap concerning the interaction between financial competence and technology adoption in the context of economic digitalization. A quantitative survey of 50 food-sector MSME actors in Blitar City who have used fintech services was analyzed using multiple linear regression. The results indicate that financial literacy has a significant and strong influence on business resilience (? = 0.47; p 0.01), while fintech adoption has a positive but more moderate effect (? = 0.22; p 0.05). The model explains 45% of the variance in MSME resilience. These findings reinforce the resource-based view theory by affirming that internal capability (financial literacy) is a key resource that is enhanced by technology (fintech) to build resilience. The implication is that MSME empowerment programs should integrate financial training with guided adoption of digital technology in a comprehensive manner